Dietary polyunsaturated fatty acids and incidence of end-stage renal disease in the Southern Community Cohort Study. Issue 1 (December 2016) - Malhotra, Rakesh; Cavanaugh, Kerri; Blot, William; Ikizler, T.; Lipworth, Loren; Kabagambe, Edmond
Abstract Background Whether polyunsaturated fatty acids (PUFA) are associated with end-stage renal disease (ESRD) in populations with a high burden of risk factors for kidney disease is unknown. We sought to determine whether PUFA intake is associated with ESRD. Methods We conducted a nested case–control study of ESRD within the Southern Community Cohort Study (SCCS), a prospective cohort of low-income blacks and whites in the southeastern US (2002–2009). Through 2012, 1, 074 incident ESRD cases were identified by linkage with the United States Renal Data System and matched to 3, 230 controls by age, sex and race. Dietary intake of total, n-3 or n-6 PUFA was assessed from a validated food frequency questionnaire administered at baseline. Odds ratios (ORs) and 95 % confidence intervals (CIs) were computed from logistic regression models that included matching variables, body mass index, smoking, diabetes, hypertension, education, income, total energy intake and percent energy from protein and saturated fat. Results The mean (SD) age of participants was 55 (9) years. Most participants were women (55 %), black (87 %), with hypertension (67 %) and on average obtained 8 % of their energy from PUFA. Higher PUFA intake was marginally associated with a lower risk of ESRD in adjusted analyses. The adjusted odds ratios (95 % confidence intervals) for ESRD for the 5th vs. 1st quintile of PUFA were 0.79 (0.60–1.05;P trend = 0.06) for total PUFA, 0.81 (0.61–1.06;P trend = 0.04) for n-6 PUFA and 0.93 (0.71–1.21;P trend = 0.45) for n-3 PUFA. Conclusions We observed a marginally significant inverse trend between dietary PUFA intake and ESRD incidence, mainly driven by n-6 fatty acid intake. Our findings require replication but suggest that a diet rich in n-6 PUFA may prevent ESRD development in a population with a high burden of kidney disease risk factors.